Atrial fibrillation among adult Saudi patients with chronic heart failure: Tertiary center experience - Al Harbi, Amjad Mohammed; Al Suhaibani, Marya Abdullah (International Journal of Health Sciences, 2018)
Objective: To estimate the rate of atrial fibrillation (AF) among adult patients with chronic heart failure (HF) from Saudi Arabia, and to identify the clinical and the demographic characteristics. Methods: This study was performed by using all medical records of patients registered in Prince Sultan Cardiac Center in Qassim (PSCCQ), Saudi Arabia and diagnosed with HF during the period from January 01, 2010 to June 30, 2014. The review process included patients diagnosed with chronic HF who were registered for follow-up during the study period. The rate of AF was calculated, and the associated risk factors were determined. Results: The rate of AF among chronic HF (n = 70) patients was 14.9%. The rate of AF was higher among males (15.7%) than females (12.5%). In both genders, the rate of AF rose with advancing age, and in each age stratum, it was higher in males than females. The rate of AF was higher if chronic HF was associated with chronic diseases, such as diabetes mellitus (DM, 14.3%), hypertension (HTN, 20%), and none of the patients had a history of chronic kidney disease (CKD). Conclusion: The rate of AF with chronic HF is high among Saudi Arabia patients. It is higher among male patients and HTN and DM patients.